Návrh marketingové strategie pro společnost Vimpex Lighting, s.r.o. - Urban, Karel (Vysoké učení technické v Brně. Fakulta podnikatelská, 2012)
Předmětem diplomové práce je vypracování návrhu marketingové strategie pro společnost Vimpex Lighting, s.r.o. Analytická část práce se opírá o teoretické poznatky a obsahuje rozbor stávající marketingové strategie společnosti. Na základě této analýzy je následně vypracován soubor doporučení, která podniku umožní dosáhnout lepší pozice na trhu a zvýšení celkové efektivity hospodaření.

Subject of the master’s thesis is creating a concept of marketing strategy for the company Vimpex Lighting, s.r.o. Analytical part of the work is based on theoretical background and contains an analysis of contemporary marketing strategy of the company. Following suggestions and recommendations reflect the results of the analysis and will help the company to reach a better position on the market and increase companies’ efectivity.
Marketing Strategy of the Company Vimpex Lighting, s.r.o.
Keywords: Marketing; marketingová strategie; marketingový mix; SWOT analýza.; Marketing; marketing strategy; marketing mix; SWOT analysis.